Implications of the Islamic Education Learning Model on Learning Outcomes During the Covid-19 Pandemic - Arnadi Arnadi; Kamal Kamal (AL-ISHLAH: Jurnal Pendidikan, 2022)
A very big challenge for educational institutions with the existence of social distancing rules where schools and offices are closed to curb infection with the coronavirus. The purpose of this study is to describe the implications of the learning model on learning outcomes during the covid-19 pandemic. This research method uses a qualitative approach with the type of case study research at two elementary schools in Sambas. Participants of this study were religion education teachers, madrasa heads, curriculum representatives, and parents of students of those schools. Data were conducted through observation and interviews. Data analysis techniques include data reduction, data presentation and conclusion drawing/verification. Meanwhile, the technique of checking the validity of the data is by extending the participation of members' checks. Research findings learning development directly and guiding children's learning at home, (b) giving birth to intensive communication so that it creates closer emotional closeness between parents and children, (c) parents can provide direct guidance to children, (d) parents can control the use of gadgets (mobile phones), (e) the creation of a collaboration between teachers and parents.